IMPLEMENTASI SISTEM INFORMASI MANAJEMEN FIREWALL DAN PENGARUHNYA TERHADAP KINERJA KARYAWAN DIVISI IT PERBANKAN - Muhamad Koerniansyah Rasjidin (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Today, the development of information technology in the banking world is very fast. The dependence of banking on information technology is very high. Innovation is always strived to have excellence in customer service than competitors. PT. Bank Danamon provides Firewall Management System services to enable every activity to gain access to each application. The purpose of this study is to analyze the effectiveness of Firewall Management system implementation in PT. Bank Danamon by adopting the DeLone and McLean models for the successful implementation of information systems. Sampling with questionnaire used in this research with 220 questionnaires distributed to users of IT infrastructure at PT. Bank Danamon, Kebon Sirih branch. Data processing and analysis in this research using SEM (Structural Equation Modeling) method with assumption hour hypothesis using AMOS (Analysis Moment of Structural) statistic software. The result of analysis shows that information quality and system quality have positive and significant effect on user satisfaction, while service quality has no effect. The results also show that user satisfaction has positive and significant impact on individual performance.  Further research can improve the model and sampling method that will be used by other financial services.